Conditions for physical modelling of the spread of contaminants in groundwater = Warunki modelowania fizycznego rozprzestrzeniania zanieczyszczeń w wodzie gruntowej - Aniszewski, Andrzej; Ciepłuch, Rafał; Laskowski, Norbert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper contains a review of dimensionless experimental dependencies determining the coefficient of transverse dispersion Dy. In the course of the dimensional analysis, dimensionless experimental dependencies describing the dispersion of pollutants in groundwater with hydraulic and physical parameters of soil in the case of steady and uniform groundwater motion were presented. The analysis allowed the determination of dimensionless practical relationships defining the dispersion factor in the perpendicular direction to the main flow direction.
Keywords: contaminants; groundwaters; dispersion coefficient; zanieczyszczenia; wody gruntowe; współczynnik dyspersji